Incidence, Risk Factors, and Evolution of Proximal Junctional Kyphosis After Posterior Hemivertebra Resection and Short Fusion in Young Children With Congenital Scoliosis. Issue 17 (1st September 2018) - Chen, Xi; Xu, Liang; Qiu, Yong; Chen, Zhong-hui; Zhu, Ze-zhang; Li, Song; Sun, Xu
Abstract : Study Design: A retrospective study. Objective: To investigate the incidence, risk factors, and evolution of proximal junctional kyphosis (PJK) in young children who underwent posterior hemivertebra resection and short fusion. Summary of Background Data: PJK is an undesired, but common complication following posterior spinal fusion. However, there is a paucity of data on PJK in young children after posterior hemivertebra resection and short fusion. Methods: This study included 189 children who had undergone posterior hemivertebra resection and short fusion (⩽4 vertebra) from January 2008 and May 2015 at a single institution. Medical records were reviewed and radiographic assessments were made preoperatively and throughout the follow-up period. Risk factors for PJK were evaluated by correlation analysis and logistic regression analysis. Results: The mean age at surgery was 4.5 years (range, 3–10 yr) and the average follow-up was 48.4 months (range, 24–87 mo). Twenty-two (11.6%) patients experienced PJK. PJK was identified within 6 months after surgery in 21 cases (95%), and the most common type was ligamentous failure. In comparison with the non-PJK group, the PJK group had greater preoperative segmental kyphosis (26.9° vs. 16.7°, P  < 0.01), longer fusion levels (3.4 vs. 2.5, P  < 0.01), and larger postoperative sagittal vertical axis (SVA; 18.9 vs. 8.6 mm, P  < 0.01). Preoperative segmental kyphosis >30°(odds ratio, 4.426), and postoperative SVA of more than 20 mm (odds ratio, 3.580) were identified as independent risk factors for PJK. In PJK group, the average proximal junctional angle increased from 4.9° to 18.5° at 6 months postoperatively, but significantly decreased to 14.8° at final follow-up. Eleven patient received brace treatment, and no patients required revision surgery. Conclusion: Despite the incidence of PJK in 11.6% of young children undergoing posterior hemivertebra resection and short fusion, no significant deterioration of proximal junctional angle were found till the last follow-up. Its risk factors include preoperative segmental kyphosis, a larger postoperative SVA and ligamentous failure. Early detection and active management may be helpful for minimizing the progression of PJK. Level of Evidence: 3